Differential Contribution of Transcription Factors to Arabidopsis thaliana Defense Against Spodoptera littoralis - Schweizer, Fabian; Bodenhausen, Natacha; Lassueur, Steve; Masclaux, Frédéric G.; Reymond, Philippe (Frontiers in Plant Science, 2013)
In response to insect herbivory, Arabidopsis plants activate the synthesis of the phytohormone jasmonate-isoleucine (JA-Ile), which binds to a complex consisting of the receptor COI1 and JAZ repressors. Upon proteasome-mediated JAZ degradation, basic helix-loop-helix transcription factors (TFs) MYC2, MYC3, and MYC4 become activated and this results in the expression of defence genes. Although the jasmonate (JA) pathway is known to be essential for the massive transcriptional reprogramming that follows herbivory, there is however little information on other TFs that are required for defence against herbivores and whether they contribute significantly to JA-dependent defence gene expression. By transcriptome profiling, we identified 41 TFs that were induced in response to herbivory by the generalist Spodoptera littoralis. Among them, nine genes, including WRKY18, WRKY40, ANAC019, ANAC055, ZAT10, ZAT12, AZF2, ERF13, and RRTF1, were found to play a significant role in resistance to S. littoralis herbivory. However, compared to the triple mutant myc234 that is as sensitive as coi1-1 to herbivory, knockout lines of these nine TFs were only partially more sensitive to S. littoralis and showed only minor gene expression changes at the whole genome level. Data thus reveal that MYC2, MYC3, and MYC4 are master regulators of Arabidopsis resistance to a generalist herbivore and identify new genes involved in insect defence.